Determinación de la capacidad de absorción visual de los componentes de las Unidades del paisaje de la Laguna del Yambo, propuesta de conservación, 2022. - Molina Suáres, Jennyfer Gabriela (2022)
The present investigation was carried out in Salcedo canton Panzaleo parish, at an altitude of 2767 meters above sea level with coordinates 768381.800N-9878619.400E in Laguna del Yambo, the objective was to determine visual absorption capacity of landscape components, methodology application to determine landscape units and through the result apply a conservation proposal. Same study that was carried out in the field, with helping guide, 7 photographs were taken where guidelines were established by Bureau of Land Management Method (BLM), and surveys application to inhabitants of the place where they allowed to establish a qualitative method. and quantitative within 7 landscape units, at the analysis of visual quality it gives us a percentage of 20.85, which means that it is in the High class where its surfaces are outstanding areas of easy regeneration, it must also take into account visual absorption where it allowed to determine that in 26.14 it has an area of average potential regeneration, it was identified as the landscape applied the methodology as well as the visual sensitivity in photograph 6 with 73, it can be deduced that the landscape of the study area is not affected even by the activities within it has a visual quality between 51 and 73 points, this means that the landscape is with high visual sensitivity, it is also necessary to take into account good environmental practices that are on conservation proposal.